2020
DOI: 10.13152/ijrvet.7.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Business Students’ Conceptions and Misconceptions of Taxes as an Input for Instruction and Curriculum Development

Abstract: Context: Tax evasion and tax compliance are important topics on a European level. Next to regulations and fines, the understanding of tax-related issues impacts a tax compliance decision. Vocational business students already pay taxes and are potential future entrepreneurs who will increasingly have to deal with tax-related issues in the future. Tax-related content is, therefore, integrated in the curriculum of business colleges in Austria. Information on business students’ conceptions and misconceptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…This study supports research on the relationship between tax knowledge and tax compliance (Fallan, 1999;Kwok & Yip, 2018;Manual & Xin, 2016;). An increase in the level of tax knowledge can lead to an increase in tax rates, where tax knowledge was related to tax avoidance (Cechovsky, 2018). In line with research (Newman & Nokhu, 2018) taxpayers have basic knowledge of taxation, but their understanding of taxes is still low.…”
Section: Rho_amentioning
confidence: 82%
See 1 more Smart Citation
“…This study supports research on the relationship between tax knowledge and tax compliance (Fallan, 1999;Kwok & Yip, 2018;Manual & Xin, 2016;). An increase in the level of tax knowledge can lead to an increase in tax rates, where tax knowledge was related to tax avoidance (Cechovsky, 2018). In line with research (Newman & Nokhu, 2018) taxpayers have basic knowledge of taxation, but their understanding of taxes is still low.…”
Section: Rho_amentioning
confidence: 82%
“…Research conducted by (Manual & Xin, 2016; found that an increase in tax knowledge level lead to tax rate increment. (Cechovsky, 2018) found that knowledge is positively related with tax attitudes and negatively related with tax avoidance. This shows that tax knowledge is an important factor for fulfilling tax obligations.…”
Section: The Dynamics Of Tax Knowledgementioning
confidence: 97%
“…Penelitian terdahulu telah menguji hubungan antara literasi keuangan terhadap kepatuhan pajak. Hasil menunjukkan bahwa literasi keuangan berpengaruh positif dan signifikan terhadap kepatuhan pajak (Hamid et al, 2019;Nichita et al, 2019), namun terdapat hasil yang berbeda yakni literasi keuangan tidak berpengaruh terhadap kepatuhan pajak (Cechovsky, 2018). Penelitian mengenai pengaruh pemanfaatan financial technology terhadap kepatuhan pajak penunjukkan hasil positif dan signifikan (Akbar & Apollo, 2020;Mu et al, 2022), namun terdapat hasil yang berbeda yakni tidak ada pengaruh antara pemanfaatan financial technology terhadap kepatuhan pajak (Masunga et al, 2020)Digitalisasi perpajakan digunakan sebagai variabel moderasi dalam memperkuat pengaruh sejumlah faktor terhadap kepatuhan pajak karena digitalisasi merupakan salah satu bentuk penerapan teknologi pada bidang ekonomi digital dan keuangan sebagai suatu sistem yang memudahkan dilakukannya kewajiban pajak (Fanea-Ivanovici et al, 2019;Ksenda, 2021).…”
unclassified